Sijunzi decoction alleviates inflammation and intestinal epithelial barrier damage and modulates the gut microbiota in ulcerative colitis mice - Li, Hailun; Pu, Xing; Lin, Yongtao; Yu, Xinxin; Li, Jing; Bo, Lin; Wang, Hongwu; Xu, Yong; Li, Xiang; Zheng, Donghui (Frontiers in Pharmacology, 2024)
Ethnopharmacological relevance: As a representative classical prescription, Sijunzi decoction has powerful therapeutic effects on spleen–stomach qi insufficiency. Ulcerative colitis (UC) is a chronic, diffuse, and non-specifically inflammatory disorder, the etiology of which still remains unclear. In the traditional Chinese medicine (TCM) perspective, splenic asthenia is the primary cause of UC. Based on this, Sijunzi decoction has been extensively used in TCM clinical practice to alleviate UC in recent years. However, the pharmacological mechanism of Sijunzi decoction in modern medicine is still not completely clear, which limits its clinical application. Aim of the study: The purpose of this study was to investigate the Sijunzi decoction’s curative effect on acute UC mice and probe into its potential pharmacological mechanism. Materials and methods: The UC mouse model was set up by freely ingesting a 3% dextran sulfate sodium (DSS) solution. The relieving role of Sijunzi decoction on UC in mice was analyzed by evaluating the changes in clinical parameters, colon morphology, histopathology, inflammatory factor content, intestinal epithelial barrier protein expression level, and gut microbiota balance state. Finally, multivariate statistical analysis was conducted to elucidate the relationship between inflammatory factors, intestinal epithelial barrier proteins, and gut microbiota. Results: First, the research findings revealed that Sijunzi decoction could visibly ease the clinical manifestation of UC, lower the DAI score, and attenuate colonic damage. Moreover, Sijunzi decoction could also significantly inhibit IL-6, IL-1β, and TNF-α while increasing occludin and ZO-1 expression levels. Subsequently, further studies showed that Sijunzi decoction could remodel gut microbiota homeostasis. Sijunzi decoction was beneficial in regulating the levels of Alistipes, Akkermansia, Lachnospiraceae_NK4A136_group, and other bacteria. Finally, multivariate statistical analysis demonstrated that key gut microbes were closely associated with inflammatory factors and intestinal epithelial barrier proteins. Conclusion: Sijunzi decoction can significantly prevent and treat UC. Its mechanism is strongly associated with the improvement of inflammation and intestinal epithelial barrier damage by regulating the gut microbiota.